Bridging Procurement Gaps Through Digital Tools: Evidence from Selected Philippine National Government Agencies - Bacarisas, Mirasol O.; Lucos, Joy Maan M.; Candelasa, Shiena Marie; Guzon, Angelica; de Fátima Marcos, Edegar; Apar-Aberia, Margareth; Malang, Bernandino P.; Malang, Jocelyn DS. (Future Science / FSH-PH Publications, 2026)
Public Procurement and its continuing agenda for transparency, efficiency and accountability in government. In the Philippines, government efforts towards digitalization seek to modernize the procurement process with systems that are intended to make bidding more accessible and transparent. Yet even with these reforms, many agencies remain plagued by delays and inefficiencies, indicating that the transition to digital platforms hasn’t gone far enough. This paper examines how digital tools can mitigate the distance between innovation and performance in public procurement. A mixed method research was utilized, combining quantitative survey analysis and quantitative inputs from sixty (60) procurement practitioner from selected national government agencies in the National Capital Region. Analyzed that the main reasons behind procurement delays and assess the digital adoption, system compatibility, staff capacity, infrastructure preparedness as well as organizational culture. Results show that digital procurement tools significantly improved transparency and reduced reliance on manual documentation, with respondents strongly aggreging on improvements in procurement cycle time (AWM = 4.28), transparency and compliance (AWM = 4.30). Additionally, many of the issues have been addressed through the digital channels by transparency and minimisation of physical paper work, however, challenges persist, particularly on the poor system integration, limited technical skills, unstable internet connectivity and resistance to digital change. Correlation analysis revealed a strong and statistically significant relationship between the extent of digital tool adoption and operational efficiency (r = 0.606, p = < 0.001), indicating that higher levels of digitalization are associated with reduced procurement delays.